Improving Failover time in Dual VIOS Network Virtualized Environment - Christila, S.Annie (The journal of contemporary issues in business and government, 2021)
Failover is a very important feature of network. Generally customers will be using dual path network environment. Whenever there is failure in one path, the path can be used and still the network communication can continue. If there is no failover setup network communication will be disturbed when there is failure in the path. Problem could on the switch / routers in that path. On virtualized environmentNetwork Interface Card(NIC) will be attached to VIOS(Virutal IO servers) and logical partitions will be sharing this NIC through virtualization technique using the bridge layer SEA (Shared Ethernet Adapter). SEA will be bridging the traffic between physical adapter and virtual adapters. Each of the LPAR(Logical Partition) will have virtual ethernet adapter (VEA) and will be communicating through SEA and physical adapter. In this paper, method to achieve faster failover when there is a failure identified in one path is being proposed in this draft.